Environmental Impact Assessment of Granite and Marble stone quarries Using RIAM and Iranian Leopold Matrix Methods - zohre rahnamabargard; Ali Sajjadi; horiye naddaf; mahnaz kharghani (Mashhad University of Medical Sciences, 2020)
Background and Aim:Regardless of the positive economic effects, the adverse environmental impacts of mines make it necessary to assess environmental impacts. The purpose of this study was to determine the environmental impacts of granite and marble quarries in Khorasan Razavi province. Materials and methods:In this descriptive-analytical study after field visits, information was collected through a checklist and data analysis was performed using RIAM and Leopold matrices. Results:Analysis of mine information through the Leopold matrix showed that the average overall ranking in all environments including cultural, socio-economic, biological and physical was -1.46, which indicates poor negative consequences. Also, the most harmful consequences were in the biological environment. According to the results of the RIAM matrix, the most negative impacts of mining occur in the physical-chemical environment. Conclusion:Exploration activities of the granite and marble quarries in Khorasan Razavi with respect to the RIAM matrix generally have moderate to slight negative effects on the physico-chemical environment and with respect to the Leopold matrix have minor adverse effects on the biological and physico-chemical environments. The continuation of exploitation of the Khorasan Razavi stone mine along with environmental considerations can, in addition to realizing the national development goals, lead to the creation of job opportunities and the construction of infrastructural facilities.